Advanced Materials as the Foundation for Innovation and National Defense - Mia Kusmiati; Sovian Aritonang; Avinash Pawar (International Forum of Researchers and Lecturers, 2025)
Purpose –The objective of this research is to analyze the role of advanced materials as a foundation for technological innovation and as a strategic element in strengthening the national defense system. The study focuses on the interrelationships between policy aspects, industry dynamics, and theoretical frameworks to explain the urgency of adopting advanced materials in Indonesia. Design/methodology/approach –This study uses a conceptual approach based on a systematic literature review (SLR) by examining reputable international publications published by Elsevier, Springer, Wiley, Taylor & Francis, IEEE, ACM, ScienceDirect, SAGE, JSTOR and DOAJ as well as national literature indexed by SINTA. The analysis was conducted using a thematic synthesis method that combines regulatory and policy dimensions, empirical data related to budget trends and industrial implementation, and theoretical models including diffusion of innovation, technology acceptance models, and behavioral reasoning theory. Findings –Studies have shown that advanced materials such as lightweight composites, high-entropy materials, smart materials, and functional coatings have a significant role in strengthening military resilience, reducing dependence on imports, and improving the efficiency of defense logistics. However, the adoption of these materials still faces obstacles such as high production costs, limited human resources, and the vulnerability of critical mineral supply chains, which are heavily influenced by global geopolitical dynamics. Practical implications –This study emphasizes the importance of strengthening national research, integrating the defense industry into the DEFEND ID ecosystem, and international collaboration to accelerate technology transfer. Mapping the critical mineral supply chain also needs to be a strategic priority to ensure the sustainability of defense materials development. Originality/value –This article offers a novel contribution through the simultaneous integration of policy perspectives, empirical data, and theoretical frameworks in the context of advanced materials development in Indonesia, an aspect that has rarely been comprehensively explored in previous studies.